Efeito vasorrelaxante de um complexo de rutênio (for0903): avaliação in situ e in silico - Simonato, Simone de Goes (2025)
The cardiovascular system has the heart as its main motor organ. When there are changes in its functioning, cardiovascular diseases occur, known as chronic non-communicable diseases, which generate consequences for the body. Among these disorders, there is hypertension, with a high prevalence in several countries. Even though it is a disease without a cure, hypertension has treatment, such as antihypertensive drugs, which have benefits, but despite them, there is a great possibility of side effects. Metallic compounds based on ruthenium have been the target of scientific research because they have potential for medical application. The main goal of this work was to evaluate the vasorelaxant effect of FOR0903 on rat aortic artery rings, in ex vivo and in silico toxicity models, as well as analyzing irritative activity in blood vessels, using the het-cam model. Cardiovascular functions can be controlled by the action of vascular smooth muscle, which has its tone modulated by the presence of the endothelium, which releases relaxing factors, such as nitric oxide (NO) and constrictors. When there is an imbalance of these factors, endothelial dysfunction occurs, which can lead to hypertension. Sodium nitroprusside is a vasodilator widely used in hypertensive crises, but it has adverse reactions. Therefore, there is a search for new compounds with vasodilator potential. This work was approved under protocol 67110523-0 by CEUA. For the experiments, adult Wistar rats were used. A new ruthenium complex FOR0903 was used. The organ bath methodology was used to evaluate vascular reactivity in the aorta artery rings, in which the animals were anesthetized and euthanized to collect the aorta and assemble it in the equipment. After the stabilization period, there was a viability test using the contractile agents phenylephrine (PHE), potassium chloride (KCl) and acetylcholine (ACh), and from then on, the experimental protocol began, using inhibitors (L -NAME, ODQ, Wortmannin, Hydroxycobalamin, L-Cysteine) to verify the pathway of participation in the vasodilatory effect of FOR0903. The het-cam model was also carried out to analyze the irritative potential of the compound, in addition to molecular docking and toxicity prediction with ADMET to evaluate the drug-receptor molecular interactions and toxic effects of the complex. The results showed that FOR0903 has a vasodilatory effect, independent of the endothelium and through stimulation of GCs, with NO donation. The het-cam showed that FOR0903 has no irritating effect and molecular docking brought acceptable affinity data between the compound and the analyzed targets (sGC and eNOS), as well as the toxicity prediction that presented favorable data for the compound, which denotes greater security to continue with the research. It is concluded that FOR0903 is a vasodilator, NO donor, with participation of the nitric oxide/guanylate cyclase (NO/GCs) pathway, without irritating effect and with low toxicity potential. More in-depth studies on the subject are needed, aiming to confirm, through more tests, the data obtained from this work with FOR0903, which could be configured, in the future, as a vasodilator used in the therapy of hypertensive patients, in favor of a better quality of life for these patients.